2016
DOI: 10.21548/34-2-1107
|View full text |Cite
|
Sign up to set email alerts
|

Cover Crops with Biofumigation Properties for the Suppression of Plant-Parasitic Nematodes: A Review

Abstract: Plant-parasitic nematodes are a problem in vineyards worldwide, with some species acting as vectors of grapevine soil-transmitted viruses. Global pressure on the use of soil-applied chemical nematicides has led to a search for new control options, or for alternative methods to suppress plant-parasitic nematodes as part of integrated pest management. This paper gives valuable background information on the use of cover crops with biofumigation properties for the suppression of plant-parasitic nematodes in vineya… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
44
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(45 citation statements)
references
References 47 publications
0
44
0
1
Order By: Relevance
“…The soil amendments were performed on samples taken at 50% anthesis, as this is the plant development stage when glucosinolate levels peak . This Brassica has shown potential as a cover crop in vineyards and as a rotation crop in rotation programmes that include annual crops, such as planting material in grapevine nurseries . We used propamocarb + fosetyl‐Al because it is widely used for the control of other soilborne diseases in horticultural Spanish nurseries and, given the lack of chemicals registered for use against black‐foot disease, its efficacy against black‐foot under field conditions had not yet been demonstrated.…”
Section: Discussionmentioning
confidence: 99%
“…The soil amendments were performed on samples taken at 50% anthesis, as this is the plant development stage when glucosinolate levels peak . This Brassica has shown potential as a cover crop in vineyards and as a rotation crop in rotation programmes that include annual crops, such as planting material in grapevine nurseries . We used propamocarb + fosetyl‐Al because it is widely used for the control of other soilborne diseases in horticultural Spanish nurseries and, given the lack of chemicals registered for use against black‐foot disease, its efficacy against black‐foot under field conditions had not yet been demonstrated.…”
Section: Discussionmentioning
confidence: 99%
“…Biofumigation, consisting of the incorporation of plant residues that slowly release their bioactive compounds into the soil, has been successfully used to control PPNs since the 19th century . Compounds resulting from field biofumigation have proven nematicidal activities, and the best example is isothiocyanates emitted by brassicas . In the last decade, studies addressing VOCs released by plant residues have revealed a number of molecules with nematicidal activity similar to commercial nematicides, therefore further studies are needed to identify VOCs emitted in biofumigation processes.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, glucosinolate concentrations and the resulting production of different forms of isothiocyanates vary greatly among Brassica species and even among cultivars within each species [58], and are also affected by environmental conditions and plant development [59,60]. This could explain in parts the lack of efficacy in reducing potato diseases in the present work, as FR is known to have moderate glucosinolate content [61] as compared to other Brassicaceae species. In addition, in the field, the expected isothiocyanates concentrations are once more lower, because of a poor release efficiency of these compounds due to incomplete tissue maceration with a mulching implement.…”
Section: Discussionmentioning
confidence: 91%